EXPERIMENTAL AND NUMERICAL INVESTIGATION OF CEMENT PASTE MICROSTRUCTURE AND ITS HYDRATION UNDER SHORT-TERM EXPOSURE TO ACETONE - Yuliia Khmurovska; Petr Štemberk; Jiří Němeček; Magdaléna Doleželová (Acta Polytechnica CTU Proceedings)
The solvent exchange methods are commonly used in order to arrest cement hydration reaction. This paper presents preliminary results of experimental investigation of cement paste microstructure under short-term (24 hours) exposure to acetone as a solvent in order to estimate the influence of solvent soaking time. The methodology to determine the effect of soaking time based on numerical prediction is also presented and described. The immersion of cement samples with the cross-section of 10×10 mm in acetone for 24 hours at the sample age of 15 hours does not enable to fully stop the hydration reaction, however, it can slow down the hydration reaction significantly. According to the comparison of several measured data (nanoindentation, scanning electron microscopy, observation made by optical microscope, mercury intrusion porosimetry) at the sample age of 1 month with the numerical simulation, the equivalent sample age is determined as approximately equal to 69 hours.